Pengaruh Pembelajaran TPS Dengan Scaffolding Konseptual Terhadap Kemampuan Menyelesaikan Masalah Sintesis Fisika - Khoirul Haniin; Markus Diantoro; Supriyono Koes H (Jurnal Pendidikan Sains, 2015)
Abstract: This study addresses the effect of TPS learning using conceptual scaffolding towards the Physics synthesis problem-solving ability in terms of the initial knowledge of Physics. This research is a quasi-experimental design with 2x2 factorial experiment. The obtained research data were analyzed by using two lanes analysis of variance (ANOVA). The results of this study showed that there are no differences in the ability to solve the problem of Physics synthesis between the groups of students who learned through TPS learning with conceptual scaffolding and TPS learning and between groups of students who have different prior knowledge. There is no effect of interaction between TPS learning strategies and conceptual scaffolding with prior knowledge to the ability to solve  physics synthesis problem.Key Words: physics synthesis problem, prior knowledge, conceptual scaffolding, TPSAbstrak: Tujuan penelitian ini adalah untuk mengetahui pengaruh pembelajaran TPS dengan scaffolding konseptual terhadap kemampuan menyelesaikan masalah sintesis Fisika ditinjau dari pengetahuan awal Fisika. Jenis penelitian ini adalah quasi experimen dengan desain faktorial 2 x 2. Data hasil penelitian eksperimen dianalisis dengan analisis variansi (ANAVA) dua jalur. Hasil penelitian menunjukkan ada perbedaan kemampuan menyelesaikan masalah sintesis Fisika antara kelompok siswa yang belajar melalui pembelajaran TPS dengan scaffolding konseptual dan pembelajaran TPS dan antara kelompok siswa yang mempunyai tingkat pengetahuan awal berbeda. Tidak ada pengaruh interaksi antara strategi pembelajaran TPS dengan scaffolding konseptual dan pengetahuan awal terhadap kemampuan menyelesaikan masalah sintesis Fisika.Kata kunci: masalah sintesis Fisika, pengetahuan awal, scaffolding konseptual, TPS